STRATEGI GURU DALAM MEMOTIVASI BELAJAR ANAK DI MADRASAH DINIYAH TAKMILIYAH AWALIYAH (MDTA) NURUL ISLAM KECAMATAN TABIR TIMUR KABUPATEN MERANGIN - Dien Muhammad Ismal Bransika, M.Pd.I; Susi Susanti (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
This research is motivated by a lack of motivation in children in the process of learning activities at Madrasah Nurul Islam. For this reason, a study was conducted which aimed to find out teacher strategies in motivating children's learning at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Nurul Islam, Tabir Timur District, Merangin Regency. This research is a descriptive research with qualitative methods, and determination of informants by purposive sampling technique, collecting data by interviews, observation and documentation. Data analysis with data reduction, data presentation and conclusion. Based on the findings of researchers at the research location through observation, interviews and documentation, it can be concluded that: the process of implementing learning at Madrasah Diniyah Takmiliyah Awaliyah Nurul Islam, Tabir Timur District, Merangin Regency begins with opening activities, core activities and closing activities. There are several obstacles faced by teachers in learning activities, namely, lack of support from parents (guardians of students), inadequate school facilities and infrastructure. The strategy used by the teacher in motivating children's learning at Madrasah Nurul Islam is by holding a competition, giving appreciation to students who excel. For this reason, it is suggested to teachers to improve learning strategies, to schools to fulfill school infrastructure, and also to need the participation of the government to provide assistance and contribute to the interests of education